Effect of frequency on cyclic response of marine clay saturated with various pore fluids. Issue 9 (21st October 2021) - Senapati, Swagatika; Banerjee, Subhadeep; T., Thyagaraj
ABSTRACT: In the present study, the cyclic triaxial tests and resonant column (RC) tests were carried out, to study the effect of frequency on reconstituted marine clay saturated with distilled water and NaCl solutions. Slurry consolidated samples were prepared at 50 kPa vertical stress. Samples were isotropically consolidated at three different effective confining pressures i.e. 80, 150 and 300 kPa. The loading frequencies adopted for the study were 0.1 Hz and 1 Hz with a number of 100 loading cycles. The results show that the effect of frequency could affect the shear modulus of clay soil reconstituted with varying pore fluid chemistry. The shear modulus increases and damping ratio decreases with increase in loading frequency for clay soil reconstituted with concentrated saline solution. Furthermore, the seismic response analysis was conducted to study the effect of frequency on marine clay soil reconstituted with distilled water and electrolyte solutions using one dimensional equivalent linear DEEPSOIL software.